Psychological Distress and Anxiety among Physiotherapists Practicing in ICU - Aniqa Tabasum, Sara Gul, Anam Shahzadi, Fariha Khalid, Muhammad Hussain Iqbal (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Fever, myalgia or fatigue, pneumonia, and complicated dyspnea are all signs of COVID-19. Chest physiotherapy can be utilized in these situations to minimize the time of stay on a mechanical ventilator and in the ICU, as well as to prevent ventilator-associated pneumonia. Aim: To determine the psychological distress and anxiety among physiotherapists in intensive care unit while performing chest physiotherapy in covid-19 patients. Methods: 176 physiotherapists were enrolled in this study, Data collected by purposive sampling technique through an online survey from physiotherapist in Lahore. The Scoring GAD-7 Anxiety Severity and Kessler Psychological Distress Scale(K10) were used. Data entered to SPSS for further statistical analysis. Results: Among 176 participants, 143(81.25%) were males and 33 (18.75%) were females.meanagewas35.11±3.752years. Psychological Distress, moderate disorder was among 26(14.6%), server disorder was among 150(85.2%). Anxiety was mild among 9(5.1%) moderate 43(24.4%) and severe 124(70.5%). P value was<0.05. Conclusion: Psychological distress and anxiety were present among physiotherapists in ICU while performing chest physiotherapy in covid-19 patients. Covid-19 affects their mental health. Most of the Physiotherapists were feeling severe anxiety and have a severe psychological Distress.